PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII HANG KESTURI SMP NEGERI 1 PEKANBARU - Weldila Fitri; Rini Dian Anggraini; Sakur Sakur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This reasearch is a classroom action research that aims to improve the learning process and improve mathematics learning outcomes by implementing the Problem Based Learning model. This research consists of two cycles, each cycle consits of four stages. The stages are, lesson planning, implementation, observation, and reflection. The mathematic quiz was given at the end of every cycles. The data needed are teacher’s activities data and student’s activites data collected by observation techniques and analyzed by descriptive statistics. The results shows that the implementation of the learning process in the second cycle improves from the first cycle. The data obtained from the student mathematics learning outcomes quizzes shows that the competence of knowledge and skills frequency of students at low and very low intervals decreases from the base score to the Quizze I score and to the Quizze II score as well as in the frequency of students at high and very high intervals increases from base score to Quiz I score and to Quiz II score. The result of this study indicates that the implementation of the Problem Based Learning model can improve the learning process and improve mathemtics learning outcomes of students in class VII Hang Kesturi SMP Negeri 1 Pekanbaru in the odd semester of the academic year 2019/2020.Key Words: Mathematics Achievement, Problem Based Learning, Class Action Research